2020
DOI: 10.1177/0192513x20980040
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and Fertility Preferences among Young Women in China: Changes over Time

Abstract: China has undergone considerable social and economic change over recent decades and, more recently, has altered its fertility policies. Using data collected at several Chinese universities from 2015 through 2019, this study examines contextual factors associated with young women’s marriage and fertility preferences. The analyses demonstrate that, over recent years, young women express a significant preference for later ages at first marriage, fewer numbers of children, and a later age at first birth. Pronatali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Specifically, individuals who are married but childless tend to lean more towards the unilateral decision-making model compared to their unmarried counterparts. Firstly, this inclination may be related to the fact that those who are married but without children are in the process of family planning [ 5 ], and in certain medical decision-making scenarios, they prefer this model. Secondly, unmarried individuals might be more reliant on their family and social networks when making medical decisions [ 1 ], hence their inclination towards a collaborative.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, individuals who are married but childless tend to lean more towards the unilateral decision-making model compared to their unmarried counterparts. Firstly, this inclination may be related to the fact that those who are married but without children are in the process of family planning [ 5 ], and in certain medical decision-making scenarios, they prefer this model. Secondly, unmarried individuals might be more reliant on their family and social networks when making medical decisions [ 1 ], hence their inclination towards a collaborative.…”
Section: Discussionmentioning
confidence: 99%
“…In the new media era, where social media and life are closely connected, various online trends deeply influence people's thoughts. At the same time, the cross-pollination of Chinese and foreign values continues to influence the importance of Chinese youth [13]. Early marriages need not be emulated, and late marriages are not anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ideas regarding family formation among Chinese international students were also associated with interpersonal situations and cultural factors. Students who reported receiving more social support from friends were more likely to report later ideal age for marriage and parenthood, which possibly reflected the overall delayed ideal ages for marriage and parenthood in the younger generation of Chinese adults (Blair & Madigan, 2021). Meanwhile, students who believed that they had stronger social support from family members in China were more likely to view China as the ideal place to live after marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with filial piety, many Chinese sexual minority people choose not to separate from but to live with or close to their families of origin (Huang & Brouwer, 2018; Lo, 2020). However, Chinese society has been changing in recent years, and a recent survey of Chinese university students suggested that they prefer older ages at marriage than did students in earlier generations (Blair & Madigan, 2021). Still, a recent study of young adult Chinese lesbian women and gay men found that traditional cultural values, such as filial piety, were important influences on their views about family formation (Wang & Zheng, 2021).…”
Section: Hypothesesmentioning
confidence: 99%